ALAT KONTROL PERALATAN LISTRIK JARAK JAUH MENGGUNAKAN BLUETOOTH BERBASIS ARDUINO NANO 3.0 - Naufal, Muhammad; Zayn, Afta Ramadhan; Ardianti, Aprillia Dwi (Al-Mantiq, 2024)
The use of electrical energy is currently less effective because many electronic equipment consumes electricity excessively. Almost all electronic devices use electricity to work. However, the situation that generally occurs is when someone uses electrical energy, it is often found that electrical energy used to turn on electronic devices is wasted due to the negligence of users who forget to turn off the device and still turn on even though it is not used. To achieve the expected goals, this study uses four stages in its development, namely: Analysis, Design, Implementation, and Testing, which can later support perfection in this research. Connectivity Not affected by weather, and very fast responsibility under 1 second at optimal distances. Testing on the Bluetooth module produces data that Bluetooth can run well as long as it is still within optimal range. System Testing produces data that the development of the Prototype with its various tests has been valid and runs according to what has been expected. In order for this prototype to function further, a device is needed to strengthen the Bluetooth signal. Make the application simpler to make it easier to use without unnecessary features, so the application will be lighter and more responsive. Provide alternative switches, so that if at any time the prototype requires maintenance will not hinder user activities.